Моtivation for Gambling in Student Population - Application of Self-Determination Theory Framework - Slađana V. Milošević (University of Belgrade, Teacher Education Faculty, 2024)
Student population is a vulnerable group of young people for involvement in gambling activities and the development of pathological gambling. The aim of this paper is to examine the nature of the motivation for gambling among students of the University of Belgrade relative to the risk of developing gambling problems. Using self-determination theory as a conceptual framework, this research investigated the motives for gambling of 158 college students, 58% female and 42% male. The socio-demographic characteristics and gambling activities of the students were additionally investigated. Data were collected using the Socio-demographic Characteristics Questionnaire, The South Oaks Gambling Screen, and The Gambling Motivation Scale. The results indicate that, out of the total number of the respondents, 10.6% of students met the criterion of being pathological gamblers, 6.96% of students are potential pathological gamblers, and 82.28% of students do not have a problem with gambling. A difference was observed in the motives for gambling. Regarding intrinsic motives, students who are pathological gamblers state the achievement of stimulation, and the extrinsic motive of coping. As for the favourite gambling activities, the following stood out: sports betting, casino, and gambling on slot machines. Students whose gambling progressed to pathological stated that they started gambling in high school and have a positive family history of gambling. The obtained results indicate the need for further research and the development of preventive programmes.